Dose–volume effect relationships for late rectal morbidity in patients treated with chemoradiation and MRI-guided adaptive brachytherapy for locally advanced cervical cancer: Results from the prospective multicenter EMBRACE study. Issue 3 (September 2016) - Mazeron, Renaud; Fokdal, Lars U.; Kirchheiner, Kathrin; Georg, Petra; Jastaniyah, Noha; Šegedin, Barbara; Mahantshetty, Umesh; Hoskin, Peter; Jürgenliemk-Schulz, Ina; Kirisits, Christian; Lindegaard, Jacob C.; Dörr, Wolfgang; et al.
Abstract: Purpose: To establish dose volume–effect relationships predicting late rectal morbidity in cervix cancer patients treated with concomitant chemoradiation and MRI-guided adaptive brachytherapy (IBABT) within the prospective EMBRACE study. Material and method: All patients were treated with curative intent according to institutional protocols with chemoradiation and IGABT. Reporting followed the GEC-ESTRO recommendations ( D 0.1 cm 3, D 2 cm 3 ), applying bioeffect modeling (linear quadratic model) with equieffective doses (EQD23 ). Morbidity was scored according to the CTC-AE 3.0. Dose–effect relationships were assessed using comparisons of mean doses, the probit model and log rank tests on event-free periods. Results: 960 patients were included. The median follow-up was 25.4 months. Twenty point one percent of the patients had grade 1 events, 6.0% grade 2, 1.6% grade 3 and 0.1%, grade 4. The mean DICRU, D 0.1 cm 3, and D 2 cm 3 were respectively: 66.2 ± 9.1 Gy, 72.9 ± 11.9 Gy, and 62.8 ± 7.6 Gy. Increase of dose was associated with increase in severity of single endpoints and overall rectal morbidity (grade 1–4) ( p  < 0.001–0.026), except for stenosis ( p  = 0.24–0.31). The probit model showed significant relationships between the D 2 cm 3, D 0.1 cm 3, and DICRU and the probability of grade 1–4, 2–4, and 3–4 rectal events. The equieffective D 2 cm 3 for a 10% probability for overall rectal grade ⩾ 2 morbidity was 69.5 Gy ( p  < 0.0001). After sorting patients according to 6 D 2 cm 3 levels, less favorable outcome was observed in the high dose subgroups, for bleeding, proctitis, fistula, and overall rectal morbidity. A D 2 cm 3  ⩾ 75 Gy was associated with a 12.5% risk of fistula at 3 years versus 0–2.7% for lower doses ( p  > 0.001). A D 2 cm 3  < 65 Gy was associated with a two times lower risk of proctitis than D 2 cm 3  ⩾ 65 Gy. Conclusions: Significant correlations were established between late rectal morbidity, overall and single endpoints, and dose–volume ( D 2 cm 3, D 0.1 cm 3 ) and dose-point (DICRU ) parameters. A D 2 cm 3  ⩽ 65 Gy is associated with more minor and less frequent rectal morbidity, whereas a D 2 cm 3  ⩾ 75 Gy is associated with more major and more frequent rectal morbidity.